Protese ocular individualizada em resina acrílica com esfera oca - Oliveira, Simone Helena Gonçalves de [UNESP] (1995)
The technique proposed aims at reducing the weight of individualized ample ocular prostheses using acrylic resins as well as simplifying laboratory procedure. For that, prefabricated hollow spheres made of plastic material, were inserted in the sclera. The average weights of the solid conventional sclera (5.30g) and those of the respective prefabricated plastic ones (3.91g) were compared. The weight reduction was significative with a confidence interval of 95% by the Student t test. ln addition, for illustration purpose, the technique was applied to patients in the ward of the Maxillofacial Prostheses Dicipline of the Dentistry School in the Campus of São José dos Campos - UNESP, having each patient received a solid prosthesis and a hollow prefabricated one made of plastic material. It has been concluded that the prostheses material spheres were inserted are lighter than the ones which received solid spheres; furthermore, thr technique is viable for ample anophtalmic cavities and requires few sessions